China's Belt and Road Initiative in Portuguese-speaking countries: Development and limits - Qiu Saiying (2022)
The Belt and Road Initiative has attracted numerous attentions from all over the world after it was unveiled. Some countries have immediately joined the initiative, while other countries have either rejected the proposal with a big NO or are taking a neutral stance and observing the development of the situation. This dissertation addresses three main questions surrounding the implementation of the B&RI by taking Portugal as a case study under the Portuguese speaking countries scope. The research analyzed official trade data, contracted projects; media articles, discourses, and interviews with state leaders; local people’s opinions were collected through semi-structured interviews to understand the practical development status of the B&RI. The aim of the study is to offer more feasible references and enlightenments to future large-scale development projects as well as for other countries, replicable and exemplary models of cooperation with China within the B&RI framework.